Abundance, diversity, and distribution of mosquito vectors in selected ecological regions of Kenya: public health implications. Issue 1 (23rd May 2013) - Lutomiah, Joel; Bast, Joshua; Clark, Jeffrey; Richardson, Jason; Yalwala, Santos; Oullo, David; Mutisya, James; Mulwa, Francis; Musila, Lillian; Khamadi, Samoel; Schnabel, David; Wurapa, Eyako; et al.
ABSTRACT: The diversity of mosquito arbovirus vectors was investigated to define regional risk of arbovirus transmission in Kenya. Mosquitoes were sampled between April, 2007 and December, 2010 at thirteen sites across seven administrative provinces and ecological zones. CDC light traps were used to collect mosquitoes while human‐landing collection was conducted in five of the sites to target day‐feeding Aedes (Stegomyia) species. Over 524, 000 mosquitoes were collected and identified into 101 species, 30 of them known vectors of arboviruses endemic to Kenya. Ae. (Neomelaniconion) mcintoshi and Ae. (Aedimorphus) ochraceus were most abundant in Garissa in the arid northeastern province, and Mansonia uniformis and Mn. africana in semi‐arid Baringo in the Rift Valley Province. Ae. ochraceus, Mn. africana and Mn. uniformis were also significant in Nyanza Province, while Ae. (Neomelaniconion) circumluteolus predominated in Budalangi, Western Province. Aedes (Stegomyia) aegypti was predominant in Rabai in the Coast Province but insignificant in the western and Nyanza sites. Culex pipiens was abundant in Rift Valley and Nyanza Provinces around the lake shores. This study highlights the potential for emergence and re‐emergence of arboviral diseases among vulnerable populations. This calls for comprehensive mapping of vector distribution and abundance for planning focused vector control measures.